Principles of Personalized Pathways for Sustainability Education: Educate, Act, Connect, and Communicate - Don Taylor; Kevin Hunt (Middle Grades Review, 2021)
Two educators describe how the model of Educate, Act, Connect, and Communicate can be utilized to address 21st century issues that concern middle grades students. The authors developed the model while using the United Nations Sustainable Development Goals (UNSDGs) to address global and local issues at two different middle schools. At Main Street Middle School, where Author One teaches, students work on the Green Team to delve deeply into the scientific and social impact of decreasing the school’s waste footprint and developing a re-use, reduce, and recycle ethos at the school. At Author Two’s school, Central Middle School, students create an eighth grade challenge that is project based, and addresses a local or global issue while aligned to the UNSDGs. The authors compare the challenges and benefits of using the Educate, Act, Connect, and Communicate framework to explore learning through the UNSDGs and make recommendations for other educators who are interested in moving toward a more integrative curriculum that highlights student voice, engagement and equity.
Keywords: personalized learning; sustainability; middle school; young adolescents